Differentially expressed genes in postperfusion biopsies predict early graft dysfunction after liver transplantation - Berberat, Pascal O.; Friess, Helmut; Schmied, Bruno; Kremer, Michael; Gragert, Stephanie; Flechtenmacher, Christa; Schemmer, Peter; Schmidt, Jan; Kraus, Thomas W.; Uhl, Waldemar; Meuer, Stefan; Büchler, Markus W.; et al. (Transplantation, 2006)
BACKGROUND: Preservation induced injury is a major contributing factor to early graft dysfunction in liver allograft recipients. We hypothesized that changes in gene expression represent the earliest indicator of ischemia/reperfusion-related injuries measurable in the graft and could be used as prognostic marker for the occurrence of graft-related complications. METHODS: We studied the expression of 67 genes, known to play a role in acute inflammatory processes by real-time polymerase chain reaction in 59 postperfusion biopsies. The level of expression was correlated with the occurrence of graft-related complications. RESULTS: We identified six genes that were significantly correlated with the occurrence of early graft dysfunction (Spearman test, two-tailed; P<0.05). High C-reactive protein (CRP) gene expression levels correlated significantly with the need of therapeutic interventions due to graft-related complications (P=0,011). Furthermore, five genes related to vascular endothelial cell physiology (CTGF, WWP2, CD274, VEGF. and its receptor FLT1) showed significantly reduced expression in the postperfusion biopsies of patients with need of therapeutic interventions due to graft-related complications in the first month (P<0.05). Using a risk score based on the expression of these five genes, complications could be predicted with 96% sensitivity (ROC analysis, specificity: 74%, positive predictive value: 72%, negative predictive value: 96%). CONCLUSION: Quantitative gene expression analysis in postperfusion biopsies may be a valuable tool to prospectively identify patients at risk for early clinical allograft dysfunction after liver transplantation.